2016
DOI: 10.1364/josab.33.000b35
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale GaP-on-diamond integrated photonics platform for NV center-based quantum information

Abstract: We present chip--scale transmission measurements for three key components of a GaP--on--diamond integrated photonics platform: waveguide--coupled disk resonators, directional couplers, and grating couplers. We also present proof--of--principle measurements demonstrating nitrogen--vacancy (NV) center emission coupled into selected devices. The demonstrated device performance, uniformity and yield place the platform in a strong position to realize measurement--based quantum information protocols utilizing the NV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
0
35
1
Order By: Relevance
“…The limiting factor for yield is the NV-cavity coupling which can be readily improved with NV-cavity registration. Furthermore, the devices were fabricated on the same chip as passive integrated photonic components [16] necessary for on-chip entanglement generation networks. Combined, these results indicate the promise of the GaP-on-diamond photonics platform for scalable quantum networks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The limiting factor for yield is the NV-cavity coupling which can be readily improved with NV-cavity registration. Furthermore, the devices were fabricated on the same chip as passive integrated photonic components [16] necessary for on-chip entanglement generation networks. Combined, these results indicate the promise of the GaP-on-diamond photonics platform for scalable quantum networks.…”
mentioning
confidence: 99%
“…Our platform utilizes a 125 nm thick GaP membrane to guide optical modes at the surface of the diamond chip [12,16], taking advantage of the high refractive index of GaP (n = 3.3) compared to that of diamond (n = 2.4). This is in contrast to the more common approach utilizing the diamond itself as the waveguiding material [17].…”
mentioning
confidence: 99%
“…Notably, achieving high conversion efficiencies requires large χ (2) , high intrinsic quality factors, critical coupling at both the fundamental and second-harmonic modes, and high nonlinear overlapÎČ. Previous work with GaP photonics on diamond [49] has indicated that the intrinsic quality factor is determined by process-dependent sidewall roughness, so the device design process was focused on achieving high mode overlap and coupling rather than increasing Q. A ring resonator topology was chosen to allow control over mode properties and independent coupling to on-chip waveguides with minimal design variables.…”
Section: Model and Designmentioning
confidence: 99%
“…GaP as a photonic platform has several attracting features: GaP provides a higher refractive index compared to diamond thus enabling waveguiding in the GaP layer. GaP features electro‐optic properties which enable optical on‐chip modulation, and well‐established fabrication processes allowing wafer‐scale processing with a high yield . Based on the GaP‐on‐diamond hybrid system, coupling of NV centers to waveguides and to optical resonators has been demonstrated.…”
Section: Coupling Color Centers To Photonic Structuresmentioning
confidence: 99%